Implementasi Strategi Think Pair Share pada Pembelajaran PAI Kelas VII di MTs Cerdas Murni - Lutfiah Aini Sitompul; Sopiyatul Bahana Harahap; Amna Riski Aulia Br. Simatupang; Arlina Arlina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study discusses the implementation of the Think Pair Share (TPS) strategy in Islamic Religious Education (PAI) learning in Grade VII of MTs Cerdas Murni, with a focus on its definition, steps, and advantages and disadvantages. This study uses a qualitative method with a phenomenological approach. The data used consist of primary data obtained through interviews and direct observation, as well as secondary data from books and journals. Data collection techniques include observation, interviews, and documentation, while data analysis is carried out through data reduction, data presentation, and verification. Data validity is tested using lingering techniques, triangulation, and negative cases. The results show that TPS is an effective cooperative learning strategy to increase student interaction and engagement. The steps in TPS include the stages of think, pair, and share. The advantage of this strategy is that it increases overall student participation, because each student is actively involved. However, the disadvantage is that it requires a relatively longer time to implement. Teachers have implemented TPS effectively, from greetings and prayers to build morals, to explaining prayer etiquette and dhikr, which enhance students' understanding, cooperation, and courage. TPS is suitable for material that requires in-depth understanding but needs to be adapted to the students' circumstances, such as using mixed methods for practical materials. Another advantage is increased student courage and critical thinking, despite challenges related to student readiness and facilities.